Current Antibiotic Treatment and Outcome for Lower Respiratory Tract Infections - Alasdair P MacGowan; Tracey Halladay; Andrew M Lovering (Canadian Journal of Infectious Diseases)
A number of national guidelines have been published to aid the antimicrobial management of community-acquired pneumonia. However, data on prescriptions for lower respiratory tract infection (LRTI) indicate considerable variation in the choice of first-line and subsequent therapy at national and local levels. Outcomes research in LRTI, whether based on clinical, economic or patient-focused criteria, is still evolving. Clinical outcomes are best studied for both pneumonia and exacerbation of chronic obstructive pulmonary disease. Economic evaluations often do not encompass all of the costs, for example, time off from work or the economic impact of antibacterial resistance. Duration of hospital stay is a good marker of costs for hospital providers and may be affected by age. marital status and comorbidities. Antibiotic choice may have an impact on the duration of hospital stay by increasing side effects, predisposing patients to hospitalacquired infection or reduced clinical efficacy. Patient expectation is largely unstudied in pulmonary infection.